Discovering communicational DNA for expressing the identity of a university - Errázuriz, Cristina (Church, Communication and Culture, 2024)
Universities with a Christian identity are particularly interested in consistency and coherence in their communications with their founding principles, mission, and purpose. Finding an essential communicational concept or DNA can help achieve this objective. Intended as the starting point for a new communications plan, this case study describes the process of finding a communicational DNA to signify the identity of the university. Internal culture is nourished by and gives meaning to the university’s identity and purpose. It is pivotal in expressing their significance in a way that resonates with the organization’s guiding values. A methodology to define a communicational DNA facilitates the development of a strategic communications plan that is aligned with the university’s identity and corporate culture and provides coherence to its brand strategy. The process considers asking key stakeholders and listening to them attentively on how they perceive the organization. A DNA approach has advantages for a university with a Christian identity as it enables the inclusion of its sense of mission within a communications plan, encompassing the specific elements of a Christian ethos. The task can shape a university’s communicational strategy and serve as a model for expressing a unique identity and purpose.